he practice of physical activity and its relationship with job satisfaction in a computer consultant - Gómez-Chacón, R.; Morales-Sánchez, V.; Hernández-Mendo, A.; Muñoz-Llerena, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
Current and modern organizations are beginning to implement health management and promotion actions in order to improve their quality of life and the productivity of the company. One of the variables that impacts productivity is job satisfaction, so the purpose of this study was to know what kind of relationship exists between the practice of physical activity and job satisfaction in Emergya, a computer consultancy. The sample consisted of 152 employees who answered the IPAQ questionnaire to assess their physical activity practice and a subjective question about job satisfaction. The results showed that there are significant differences, being the practitioners of vigorous physical activity (M = 4,19), the practitioners of moderate physical activity (M = 4,15) and the practitioners of low physical activity (M = 3,38). Therefore, the findings conclude that the practice of physical activity, in a vigorous and moderate way, positively influences the job satisfaction of employees.